2020
DOI: 10.1016/j.apergo.2020.103112
|View full text |Cite
|
Sign up to set email alerts
|

Operationalizing resilient healthcare concepts through a serious video game for clinicians

Abstract: Resilient healthcare emphasises the importance of adaptive capacity for the quality of healthcare. It has had extensive theoretical development, but comparatively limited translation for clinicians in practice. This study was the first in the world to present resilient healthcare principles in a serious video game. Serious games are an effective tool for engaging users, sharing ideas and eliciting reflections. The purpose of this study was to communicate principles from resilient healthcare to clinicians throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
(34 reference statements)
0
18
0
Order By: Relevance
“…Some teachers also encourage students to use low-internet data applications (Tuli et al, 2020) and free sites, such as low-cost e-learning (Brown et al, 2020;Jackson et al, 2020;Yuhasriati et al, 2020), as not every school provides internet data subsidy for students and teachers. So, teachers implement the distance learning strategy by recommending free online learning apps for students.…”
Section: Discussionmentioning
confidence: 99%
“…Some teachers also encourage students to use low-internet data applications (Tuli et al, 2020) and free sites, such as low-cost e-learning (Brown et al, 2020;Jackson et al, 2020;Yuhasriati et al, 2020), as not every school provides internet data subsidy for students and teachers. So, teachers implement the distance learning strategy by recommending free online learning apps for students.…”
Section: Discussionmentioning
confidence: 99%
“…If students and lecturers choose synchronously, most of them combine WhatsApp with other platforms like Google Classroom. Based on data and signal limitations, many lectures also encourage students to use low-internet data applications (Tuli et al, 2020)and free sites, such as low-cost e-learning (Azhari et al, 2020;Brown et al, 2020;Jackson et al, 2020), as not every HEI provides internet data subsidy for students and lectures.…”
Section: E-learning Tools Used By Studentsmentioning
confidence: 99%
“…Recent research has indicated that the creation of re ective spaces, where different stakeholders have the opportunity to meet and exchange experiences within and across levels has the potential to bridge tacit and explicit knowledge, and thereby create awareness [21]. Creating spaces for re ection that can facilitate mindfulness and awareness towards clinical practice, the choices that are made, and why, has been suggested as promising in other contexts [21,31,32,55]. Creating re exive spaces for stakeholders across different system contexts and levels could therefore potentially create higher awareness and understanding among different stakeholders and their roles in a complex adaptive healthcare system.…”
Section: Re Ection and Awareness -A Key To Successful Adaptationsmentioning
confidence: 99%
“…Most frequently resilience studies adress learning as an outcome, pointing at speci c adaptive practices to handle capacity-demand misalignments, such as workarounds [26], secret second handovers [27], or next of kin agency [28,29]. More recently, some studies have focused on developing speci c tools for strengthening resilient capacities, such as serious games [30][31][32][33] and re ective spaces or narratives [12,21]. However, resilience studies are frequently tightly focused on individual learning,such as people-technology interaction [34], or openness for change,- [35], with only limited focus on team learning or collaborative learning approaches.…”
Section: Introductionmentioning
confidence: 99%